Pessoa, lugar e esperança : teologia e literatura em vidas secas - Bauwelz, Joanicio Fernando (2018)
This dissertation is a dialogue of theology with literature, to know the person and their hopes in the world of life, in search of a narrative that contribute in the growing of the theological knowledge. The chosen work is Vidas Secas from Graciliano Ramos, that perfectly translates the person and the tension with the dry reality in which they live and seek to provide a major meaning to their existence. The first chapter contextualizes the dialogue between theology and literature from the historical view, of theologians of relevance and their methods. The second chapter demonstrates the direct influence of the lived experiences by Graciliano Ramos in the shape and in the content of the book. The third chapter, through the anthropological method of Manzatto, analyzes Vidas Secas by the binomial person and place. The fourth chapter continues the anthropological reflection by the concept of hope, as element that intends the person in the search of the realization of their happiness and provides meaning to suffering. For this, uses the hermeneutical method of Divo Barsotti. In Vidas Secas the perspective of hope is present in the sertaneja religiosity and in the symbols of hope from the characters. This is a possible dialogical approach, among others, of theology with literature.